A biojuridical reminder on the vulnerability and dignity of critical patients - Pacheco Leyton, Adriana (2020)
Today, the pandemic caused by COVID-19 has abruptly shown us a reality that no one escapes: the mystery of human nature that is death. Human life cannot be explained without death. And it is that the moment of death is as important as that of birth because it is part of the natural process of life. The truth is that the pandemic brings with it pain and suffering prior to death; and it is of such a lethality that, despite existing risk groups, we are all exposed to contagion.The speed with which the virus spreads and the inability to contain its effects, has caused the death of millions of people around the world, which leads us to look at the places where death is faced on the front line. . But the most important thing is that it leads us to look at the fragility of life from another perspective.Critically ill patients (that is, with severe deterioration in their organic functions due to diseases that can potentially be complicated by compromising life), keep their dignity intact and, being a fragile group in extreme circumstances such as a pandemic, leave evidence of that violate the dignity of people in the field of health care activity, for which we believe it is important to remember from a bio-legal perspective, the vulnerability of critically ill patients.